Analisis Bahan Instruksional di SDN Pondok Jagung 2 - Putri Alifia Mediana; Nursiah Nursiah; Lathifah Shansabilah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
From the results of the study that SDN Pondok Jagung 2 in the design of learning in high classes is more likely to prioritize practical methods, lecture methods and use media such as pictures in the teaching and learning process so that teachers know the development and creativity of children in school, but teachers must also know the development and nature of individuals child. And SDN Pondok Jagung 2 uses a group learning model because it follows the rules of Curriculum13 and the number of stundents in each class.